Faktor-Faktor Krisis Dan Dampak Krisis Yang Pernah Terjadi Di Indonesia Sehingga Mengakibatkan Kerapuhan Fundamental - Dwi Nur Maulidia; Mohammad Ricko Kurniawan; Muhammad Yasin (Student Scientific Creativity Journal, 2023)
A crisis experienced by a country will affect a country's fundamentals or foundation because the impact is so great and can be felt by all levels of society in the country, both the government and society in general. This study will analyze the factors and impact of the crisis on the fragility of fundamentals. This research uses a descriptive analysis method, namely to investigate the situation, condition, the results of which are presented in the form of a research report with what it is about the crises that have occurred in Indonesia from 1960 to 2021. thus triggering inflation, deflation, and even recession which makes the crisis of society and government and affects its fundamental resilience.